Thiol/redox metabolomic profiling implicates GSH dysregulation in early experimental graft versus host disease (GVHD). - Jung H Suh (Public Library of Science (PLoS), 2014)
Graft-versus-host disease (GVHD) is a common complication of allogeneic bone marrow transplantation (BMT). Upregulation of inflammatory cytokines precedes the clinical presentation of GVHD and predicts its severity. In this report, thiol/redox metabolomics was used to identify metabolic perturbations associated with early preclinical (Day+4) and clinical (Day+10) stages of GVHD by comparing effects in Syngeneic (Syn; major histocompatibility complex- identical) and allogeneic transplant recipients (Allo BMT) in experimental models. While most metabolic changes were similar in both groups, plasma glutathione (GSH) was significantly decreased, and GSH disulfide (GSSG) was increased after allogeneic compared to syngeneic recipient and non-transplant controls. The early oxidation of the plasma GSH/GSSG redox couple was also observed irrespective of radiation conditioning treatment and was accompanied by significant rise in hepatic protein oxidative damage and ROS generation. Despite a significant rise in oxidative stress, compensatory increase in hepatic GSH synthesis was absent following Allo BMT. Early shifts in hepatic oxidative stress and plasma GSH loss preceded a statistically significant rise in TNF-α. To identify metabolomic biomarkers of hepatic GVHD injury, plasma metabolite concentrations analyzed at Day+10 were correlated with hepatic organ injury. GSSG (oxidized GSH) and β-alanine, were positively correlated, and plasma GSH cysteinylglycine, and branched chain amino acids were inversely correlated with hepatic injury. Although changes in plasma concentrations of cysteine, cystathionine (GSH precursors) and cysteinylglycine (a GSH catabolite) were not significant by univariate analysis, principal component analysis (PCA) indicated that accumulation of these metabolites after Allo BMT contributed significantly to early GVHD in contrast to Syn BMT. In conclusion, thiol/redox metabolomic profiling implicates that early dysregulation of host hepatic GSH metabolism and oxidative stress in sub-clinical GVHD before elevated TNF-α levels is associated with GVHD pathogenesis. Future studies will probe the mechanisms for these changes and examine the potential of antioxidant intervention strategies to modulate GVHD.